Interpretasi Adjektiva terhadap Fisiko-Kimia Nasi dari Beras Organik dan Non-Organik Varietas Pandan Wangi Sidrap - Salfiana Salfiana; Andi Nurwidah; Eka Pratiwi Safri (Universitas Teuku Umar, 2026)
This study aims to analyze the interpretation of adjectives on the physico-chemical properties of rice from organic and non-organic rice varieties Pandan Wangi Sidrap. This study measured physico-chemical characteristics such as color, ash content, and moisture content in rice cooked with various water ratios and types of rice. The methods used included testing with a colorimeter to analyze the degree of whiteness of rice, as well as testing ash content and moisture content. The results showed that rice from organic rice tended to have a higher moisture content (56.22% - 63.46%) compared to rice from non-organic rice (55.75% - 62.61%), which affected the softer texture of rice in organic rice. Ash content measurements showed higher values in non-organic rice, indicating differences in mineral content between the two types of rice. Color testing showed significant differences between rice from organic and non-organic rice, with organic rice tending to have a darker and more yellowish color. In addition, the results of organoleptic tests showed that rice from organic rice was preferred in terms of aroma, texture, and taste compared to rice from non-organic rice. Overall, this study revealed that rice type, water ratio, and farming techniques play an important role in influencing the physico-chemical and sensory qualities of rice, which ultimately influence consumer acceptance of the rice product.